The Use of Shopping Apps among Smartphone Users in China: A Structural Equation Modelling Approach - Muhammad Tahir Jan; Li Yao (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
Along with the continuous advancement of technology, people are enjoying the benefits of implementing it in their daily lives. Using smartphone applications (apps) to shop is growing dramatically and creating new business opportunities for vendors. The main purpose of this research is to accomplish a measurement model of the use of mobile shopping apps among smartphone users in China through extended technology acceptance model (TAM). Smartphone users from mainland China who use the m-shopping applications were selected randomly for data collection. The questionnaire was distributed through a survey website. A number of 281smartphone users participated in this online survey and 234 of them were selected for final data analysis. The data was analysed by two statistical tools, which are IBM SPSS Statistics 24 and AMOS 24. Both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were utilized to measure construct reliability and validity. Structural equation modelling (SEM) was deployed for inferential data analysis. The finding presented that perceived usefulness (PU), perceived ease of use (PEoU), information on mobile apps (IoMA) and perceived enjoyment are all influential factors for consumers to use m-shopping apps. Especially the perceived enjoyment (PE) and IoMA have an influence on usage. However, the performances of these three constructs are not executed well in term of consumer satisfaction.